2022
DOI: 10.3390/clinpract12010013
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices toward First Aid Management of Skin Burns in Saudi Arabia

Abstract: Background: Burns are considered a serious health affection that leads to several consequences affecting a person both physically and emotionally. Herbal and traditional medicine have become popular remedies among patients worldwide. Aim: This study explores common practices followed in burns as first aid management. Methods: A cross-sectional study was conducted in the Eastern province of Saudi Arabia using a designed questionnaire distributed electronically through different social media. The questionnaire c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 22 publications
1
25
1
Order By: Relevance
“…Another study from Pakistan in Rawalpindi found that the two most often used items after a burn injury were toothpaste (47.5%), followed by cool running water (20.3%), while in Nigeria, water lavage was used in 49 (29.2%) instances, raw eggs in 21 (12.5%), and pap in 16 (9.5%) [19]. Similar findings in two studies by Almutlaq BA et al (2020) [20] and Al Dhafiri M et al (2022) [21] conducted in Saudi Arabia found that the majority of participants utilized cold water or honey as post-burn therapy. Although studies have shown that consuming honey does not significantly reduce the amount of burned tissue, it has recently been shown that using honey and silver sulfadiazine together can speed up healing burn wounds [22].…”
Section: Discussionsupporting
confidence: 70%
“…Another study from Pakistan in Rawalpindi found that the two most often used items after a burn injury were toothpaste (47.5%), followed by cool running water (20.3%), while in Nigeria, water lavage was used in 49 (29.2%) instances, raw eggs in 21 (12.5%), and pap in 16 (9.5%) [19]. Similar findings in two studies by Almutlaq BA et al (2020) [20] and Al Dhafiri M et al (2022) [21] conducted in Saudi Arabia found that the majority of participants utilized cold water or honey as post-burn therapy. Although studies have shown that consuming honey does not significantly reduce the amount of burned tissue, it has recently been shown that using honey and silver sulfadiazine together can speed up healing burn wounds [22].…”
Section: Discussionsupporting
confidence: 70%
“…First aid is the deliverance of immediate and initial care for an accident before medical treatment can be provided. [ 1 2 ] Injuries are the leading cause of morbidity and mortality worldwide, particularly in developing countries. [ 3 ] First aid procedures include basic knowledge of medical skills that a person can provide, whether with or without a formal medical background.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they should be capable of providing first aid in cases of health-related emergencies. 13 , 14 However, there is limited evidence on the knowledge and practice of basic first aid among schoolteachers and people in the community. 15 Therefore, it is vital to provide schoolteachers with information and skills regarding basic first aid.…”
Section: Introductionmentioning
confidence: 99%